Specialized attachment structure of the fish pathogenic oomycete Saprolegnia parasitica. - Svetlana Rezinciuc; Jose Vladimir Sandoval-Sierra; Yolanda Ruiz-León; Pieter van West; Javier Diéguez-Uribeondo (PLoS ONE, 2018)
The secondary cysts of the fish pathogen oomycete Saprolegnia parasitica possess bundles of long hooked hairs that are characteristic to this economically important pathogenic species. Few studies have been carried out on elucidating their specific role in the S. parasitica life cycle and the role they may have in the infection process. We show here their function by employing several strategies that focus on descriptive, developmental and predictive approaches. The strength of attachment of the secondary cysts of this pathogen was compared to other closely related species where bundles of long hooked hairs are absent. We found that the attachment of the S. parasitica cysts was around three times stronger than that of other species. The time sequence and influence of selected factors on morphology and the number of the bundles of long hooked hairs conducted by scanning electron microscopy study revealed that these are dynamic structures. They are deployed early after encystment, i.e., within 30 sec of zoospore encystment, and the length, but not the number, of the bundles steadily increased over the encystment period. We also observed that the number and length of the bundles was influenced by the type of substrate and encystment treatment applied, suggesting that these structures can adapt to different substrates (glass or fish scales) and can be modulated by different signals (i.e., protein media, 50 mM CaCl2 concentrations, carbon particles). Immunolocalization studies evidenced the presence of an adhesive extracellular matrix. The bioinformatic analyses of the S. parasitica secreted proteins showed that there is a high expression of genes encoding domains of putative proteins related to the attachment process and cell adhesion (fibronectin and thrombospondin) coinciding with the deployment stage of the bundles of long hooked hairs formation. This suggests that the bundles are structures that might contribute to the adhesion of the cysts to the host because they are composed of these adhesive proteins and/or by increasing the surface of attachment of this extracellular matrix.